Correlation between pre‐procedural plaque morphology and patterns of in‐stent neointimal hyperplasia at 1‐year follow‐up in patients treated with new‐generation drug‐eluting stents: An optical coherence tomography based analysis - Shi, Shun‐Yi; Chen, Kai‐Lun; Gu, Jue; Xu, Chen; Chen, Qian‐Ru; Chen, Yu‐Qiao; Xu, Tian; Ke, Hai‐Yan; Sun, Jian‐Hui; Ye, Fei (Journal of interventional cardiology, 2018)
Instruction Several factors affect the in‐stent intimal healing process after drug‐eluting stents (DESs) implantation. We hope to investigate the influence of plaque characteristics on subsequent heterogeneous neointimal hyperplasia (NIH) using optical coherence tomography (OCT). Methods The study population consisted 217 patients with single‐vessel de novo lesions who underwent both pre‐procedural OCT scan and 12‐month follow‐up OCT examination. NIH is defined as at least five consecutive cross‐sectional images with no less than 100µm neointimal thickness. According to OCT follow‐up, patients were divided into three groups: neointima‐covered group, homogeneous, and heterogeneous NIH group. Results 102 patients were categorized in neointima‐covered group, 91 and 24 patients in homogeneous and heterogeneous group, respectively. Time interval between OCT scans was similar (P = 0.55). No significant differences in the patients’ age, gender, comorbidities, laboratory findings, procedural, and lesion‐related findings were found among these three groups. Heterogeneous group tended to have more subjects presented as acute coronary syndrome (ACS) (P = 0.04) and mean macrophage grade was higher in this group (P = 0.01). While no statistically significant difference concerning mean intimal thickness (P = 0.21) or neointimal burden (P = 0.73) was found between homogeneous and heterogeneous group. Multivariate logistic regression analysis showed that mean macrophage grade (OR: 2.26, 95%CI: 1.12 to 4.53, P = 0.02) and initial clinical presentation of ACS (OR: 2.81, 95%CI: 1.03 to 7.72, P = 0.04) were significant independent risk factors for heterogeneous NIH. Conclusion Mean macrophage grade measured by OCT as a semi‐quantitative morphological risk factor, as well as clinical presentation of ACS, was associated with in‐stent neointimal heterogeneity after DES implantation.